Photodynamic inactivation for in vitro decontamination of Staphylococcus aureus in whole blood - Correa, Thaila Quatrini; Blanco, Kate Cristina; Soares, Jennifer Machado; Inada, Natalia Mayumi; Kurachi, Cristina; Golim, Marjorie de Assis [UNESP]; Deffune, Elenice [UNESP]; Bagnato, Vanderlei Salvador (Elsevier B.V., 2019)
Background: Blood can be the target of microbial cells in the human body. Erythrocytes, platelets, and plasma concentrates in blood bags used in hemotherapy for blood transfusion are contamination targets, which can trigger serious diseases in blood. These infections can cause septicemia that can lead to death if not recognized rapidly and treated adequately. The aim of this study was to evaluate the photodynamic inactivation in the in vitro decontamination of Staphylococcus aureus in whole blood, erythrocytes and platelet-rich plasma. Methods: Photodynamic inactivation using light doses of 10, 15 and 30 J/cm(2) at 630 nm and an hematoporphyrin-derivative photosensitizer (Photogem (R)) solutions at 25 and 50 mu g/mL were evaluated. Toxicity of treatment was determined by hemolysis and cell viability assays. Results: The S. aureus reduction in phosphate buffered saline (PBS), whole blood, erythrocytes and platelet-rich plasma at 15 J/cm(2) and 50 mu g/mL were 7.2, 1.0, 1.3 and 0.4 log CFU/mL, respectively. Quantitative and qualitative analyses were performed in whole blood samples, and Photogem (R) showed a low risk of hemolysis (10.7%) in whole blood. However, 100% of erythrocytes suffered hemolysis in the absence of plasma. The cell viability assay showed 13.9% of apoptosis in erythrocytes, but normal platelet viability. Conclusion: S. aureus inactivation of whole blood samples using 50 mu g/mL Photogem (R) and 15 J/cm(2) resulted in better outcomes, providing promising indications for treatment of bacterial contamination of blood, and in this work, alternative possibilities to apply the technique for blood decontamination are discussed.
Keywords: Photodynamic inactivation; Blood; Decontamination; Staphylococcus aureus